Overexpression of SAMDC1 gene in Arabidopsis thaliana increases expression of defense-related genes as well as resistance to Pseudomonas syringae and Hyaloperonospora arabidopsidis - Marco, Francisco; Busó, Enrique; Carrasco, Pedro (Frontiers in Plant Science, 2014)
It has been previously described that elevation of endogenous spermine levels in Arabidopsis could be achieved by transgenic overexpression of S-Adenosylmethionine decarboxylase (SAMDC) or Spermine synthase (SPMS). In both cases, spermine accumulation had an impact on the plant transcriptome, with up-regulation of a set of genes enriched in functional categories involved in defense-related processes against both biotic and abiotic stresses. In this work, the response of SAMDC1-overexpressing plants against bacterial and oomycete pathogens has been tested. The expression of several pathogen defense-related genes was induced in these plants as well as in wild type plants exposed to an exogenous supply of spermine. SAMDC1-overexpressing plants showed an increased tolerance to infection by Pseudomonas syringae and by Hyaloperonospora arabidopsidis. Both results add more evidence to the hypothesis that spermine plays a key role in plant resistance to biotic stress.